The Effectiveness of E-Learning Madrasah in English Teaching and Learning - Aris Purwantoro; Slamet Asari; Nirwanto Maruf (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Covid-19 pandemic is consider as global pandemic since February 2020 by World Health Organization (WHO), it forces education system shifted into online learning. E-learning madrasah as a tool for online teaching and learning process issued by Ministry of Religion Affairs are considered very effective and useful as online learning and teaching during Covid-19 pandemic. This study investigated students’ and teachers’ perceptions, and the effectiveness of e-learning madrasah in English teaching and learning. A mixed qualitative and quantitative methods was used to reveal 362 students’ and 13 teachers’ perceptions and the effectiveness of e-learning madrasah at Islamic state junior high schools (MTSN) in Lamongan regency, East Java, Indonesia. The finding revealed that e-learning madrasah as a tool in teaching and learning process is considered useful during Covid-19 pandemic outbreak, students are motivated to join their English class, and students perceived that this learning tool is ease to utilize as well. In term of teachers’ perceptions indicates the same way as students’. They perceived that this e-learning system as a tool of teaching and learning was very useful and ease to use. Also, they perceived that the system of this e-learning madrasah in term of system was not difficult to be implemented in teaching and learning process.